Utilization of Innovation and Business Diversification by Village-Owned Enterprises in Indonesia - Roby Syaiful Ubed; Mohamad Syamsul Maarif; Marimin Marimin; Asep Taryana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Village-Owned Enterprises in Indonesia face challenges in increasing the resilience, competitiveness, and empowerment of rural communities. Therefore, business diversification is an important strategy to support inclusive development. This study examines the utilization of business diversification techniques by village-owned enterprises in Indonesia to improve resilience, competitiveness, and empower rural communities. Employing a grounded theory methodology, data were gathered via comprehensive interviews and focus group discussions with principal stakeholders of village-owned enterprises. The coding method, which included open, axial, and selective coding with NVivo 12, produced a theoretical framework elucidating the determinants, strategies, and consequences of village-owned enterprises diversification. The results indicate that effective diversification is influenced by four interconnected factors: innovation, collaborative governance, digital transformation, and community participation. Janti Jaya village-owned enterprises had substantial growth via agrotourism, e-ticketing, Micro, Small, and Medium Enterprises facilitation, and Corporate Social Responsibility collaborations, generating IDR 4 billion in revenue during the first semester of 2023 and receiving acknowledgment as one of the Top 15 “Desa Brilian.” Karunia Sejahtera VOE utilized Umbul Ngrundul’s tourism and digital services to strengthen sustainability, while the study extends grounded theory and offers policy insights on innovation, governance, and collaboration for inclusive rural development.